Konsep tabayun dalam Islam dan kaitannya dengan informasi - Gusnar Zain (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2017)
Islamic is a religion that governs the relationship between man and God, between human beings and man with the natural surroundings, called Shari'ah. The rules of Islam are universal-universal, not everyone can understand them easily and perfectly. To understand Islam in a perfect, detailed-partical way, it is necessary to find the explanation by understanding the context of the sentence literally and literally-implied by the system And classification of existing data and facts, this is called information, that is seeking an explanation or truth about something that happened.